2022
DOI: 10.3390/antiox11112191
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Phenolic Metabolites in Urine Are Inversely Linked to Certain Features of Metabolic Syndrome in Spanish Adolescents

Abstract: (1) Background: To explore the association between microbial phenolic metabolites (MPM) and metabolic syndrome (MetS) and its clinical features in adolescents aged 12.02 ± 0.41 years. (2) Methods: a cross-sectional study was conducted in 560 participants at baseline in the SI! Program for Secondary Schools trial. The following MPM, coumaric acids (m-, o-, p- coumaric acids), dihydroxyphenylpropionic acid, dihydroresveratrol, enterolignans, gallic acid, hydroxybenzoic acids, hydroxyphenylacetic acid, hydroxytyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Different cartridges (C18 Sep-pack, Supelclean LC-C18, Bond Elut C18, Oasis HLB, MCX) were chosen for the different samples, and in all cases, water was used as the washing solvent and MeOH as the elution solvent. In some cases, ninety-six well micro-elution SPE was employed, as it is useful for low volumes of samples and it can facilitate high-throughput sample processing [103,[165][166][167][168]180,181,184,185,188,[208][209][210].…”
Section: Extraction Of Uros From Biological Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Different cartridges (C18 Sep-pack, Supelclean LC-C18, Bond Elut C18, Oasis HLB, MCX) were chosen for the different samples, and in all cases, water was used as the washing solvent and MeOH as the elution solvent. In some cases, ninety-six well micro-elution SPE was employed, as it is useful for low volumes of samples and it can facilitate high-throughput sample processing [103,[165][166][167][168]180,181,184,185,188,[208][209][210].…”
Section: Extraction Of Uros From Biological Samplesmentioning
confidence: 99%
“…HPLC and UHPLC were the most common methods employed for the separation of Uros, using reverse phase columns with octadecyl-bonded stationary phases and isocratic or gradient mobile phases consisting of water mixed with acetonitrile or methanol with the addition of formic or acetic acid. In rare cases, a pentafluorophenylpropyl (F5) phase column and an ether-linked phenyl phase column were also successfully utilized for the separation of Uro conjugates [170,208]. The detection and quantification of analytes was usually achieved with the use of UV-diode array detec-tors (DAD) or photodiode array detectors (PDA) coupled in series with mass spectrometers, such as ion traps (IT) [5,162,[165][166][167]173,175,180,204,205,208,211], triple quadrupoles (QqQ) [168,171,172,174,189,190,192,193,196,199,200,209,212,213], and quadrupole-time of flight (QTOF) systems with electrospray ionization (ESI) sources [169,[177][178][179]182,183,191,203,207].…”
Section: Analytical Techniques For the Determination Of Urosmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a panel of experts on (poly)phenols has developed the first-ever guideline recommendations for dietary flavanol or flavan-3-ol intake, highlighting the role of this subclass of flavonoids in the prevention of cardiometabolic diseases in adults [8]. Nevertheless, to date, few studies about (poly)phenols and cardiometabolic health have been carried out in adolescents, generating the question of whether dietary (poly)phenols could have an effect on cardiometabolic health in this target population [9][10][11][12][13][14][15]. In the HELENA study, Wisnuwardani et al estimated dietary (poly)phenol intake in European adolescents through 2 non-consecutive 24h dietary recalls, and they found associations between total (poly)phenol intake (TPI) and body mass index (BMI) in a cross-sectional analysis and between lignan intake and a lower metabolic syndrome risk over time [9,10,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, in previous studies, we found that total (poly)phenols in urine, as a biomarker of (poly)phenol intake, and some individual microbial phenolic metabolites such as urolithins and gallic acid were associated with better cardiometabolic health parameters in adolescents who participated in the SI! (Salud Integral-Comprehensive Health) Program for Secondary Schools, a large cohort in Spain [11,12,14,15]. However, information about long-term exposure to dietary (poly)phenols, including (poly)phenol subclasses (flavonoids, phenolic acids, stilbenes, and lignans), assessed with a widely used dietary tool, is needed to understand the plausible relationship between the intake of these bioactive compounds and cardiometabolic health in this cohort.…”
Section: Introductionmentioning
confidence: 99%